Pelestarian Bahasa Daerah Tanimbar Sebagai Upaya Perlindungan Ekspresi Budaya Tradisional - Sasya Luturmas; Teng Berlianty; Agustina Balik (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: This study discusses the preservation of the Tanimbar regional language as an effort to protect traditional cultural expressions in the use of 5 (five) Tanimbar regional languages, namely East Yamdena, Fordata, Selaru, Selwasa, Makatian languagesPurposes of the Research: To find out and analyze how the preservation of the Tanimbar regional language as an effort to protect traditional cultural expressions.. Methods of the Research: This study uses an empirical juridical method by describing or providing an overview of the object under study through interviews and observations.Results of the Research: The results showed that the use of the Tanimbar regional language in 5 regional languages, namely Fordata, East Yamdena, Selwasa, Selwasa and Makatian the number of speakers was very limited or few. Based on the results of the language strength scale, the Tanimbar regional language is in danger of extinction. The inhibiting factor of the Tanimbar regional language is threatened because most parents (families) do not use the local language when communicating with children but prefer to use Ambonese Malay. By re-activating the Tanimbar regional language, the Village Community Empowerment Foundation collaborates with social and religious institutions in equipping local teams with programs for developing reading materials, local content materials, local curriculum content as well as translating spiritual songs, scriptures, sermons, and sing in the local language.